2020
DOI: 10.38001/ijlsb.656112
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Antidiarrhoeal Activity of Aqueous Root and Stem Bark Extract of Annona Senegalensis.

Abstract: Diarrhoea is a leading cause of deaths amongst children below five years. Annona senegalensis plant is used traditionally to treat diarrhoea. This study aims at evaluating the antidiarrhoeal potency of the aqueous root and stem bark extracts of Annona senegalensis. Antimicrobial, antioxidant and antidiarrhoeal activity of aqueous extracts of the root bark (ARB), stem bark (ASB) and mixture of stem and root barks (AM) of Annona senegalensis were assessed. Stool inhibition, enteropooling, inhibition of gastro-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 28 publications
(30 reference statements)
0
8
0
Order By: Relevance
“…Moreover, Ahmed reported that the H 2 O 2 scavenging activity and the ferric reducing assay power of A. senegalensis extracts was significantly greater (p < 0.05) than ascorbic acid. The same author reported that the ferric thiocyanate scavenging activity and thiobarbituric acid (TBA) activity of all the extracts of A. senegalensis were significantly greater (p < 0.05) than that of ascorbic acids [30].…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, Ahmed reported that the H 2 O 2 scavenging activity and the ferric reducing assay power of A. senegalensis extracts was significantly greater (p < 0.05) than ascorbic acid. The same author reported that the ferric thiocyanate scavenging activity and thiobarbituric acid (TBA) activity of all the extracts of A. senegalensis were significantly greater (p < 0.05) than that of ascorbic acids [30].…”
Section: Discussionmentioning
confidence: 98%
“…senegalensis plant has been demonstrated properties including antibacterial (Ahmed et al, 2020;Lall et al, 2017), anticonvulsant, antiinflammatory (Konaté et al, 2021;Tamfu et al, 2021), antidiarrhea (Ahmed et al, 2020;Djoza et al, 2017), antimalarial (Ngwewondo et al, 2019), smooth muscle relaxant (Adisa et al, 2019), and sedative, central nervous depressant, and anticonvulsant (Adisa et al, 2019).…”
Section: Hibiscetin Kaempferol Luteolinmentioning
confidence: 99%
“…In Benin, Nigeria, Togo, for example, local livestock farmers depend on the plant as an anthelminthic. A. senegalensis plant has been demonstrated properties including antibacterial (Ahmed et al, 2020; Lall et al, 2017), anticonvulsant, anti‐inflammatory (Konaté et al, 2021; Tamfu et al, 2021), antidiarrhea (Ahmed et al, 2020; Djoza et al, 2017), antimalarial (Ngwewondo et al, 2019), smooth muscle relaxant (Adisa et al, 2019), and sedative, central nervous depressant, and anticonvulsant (Adisa et al, 2019). The usefulness of the plant for medicinal purposes has been attributed to the presence of bioactive compounds (phytochemicals) including alkaloids (Inkoto et al, 2018), anthocyanins (Konaté et al, 2021), flavonoids (Lall et al, 2017), glycosides (Musa et al, 2017; Tamfu et al, 2021), steroids (Konaté et al, 2021), tannins (Musa et al, 2017), and saponins and volatile oils (Ibrahim et al, 2019).…”
Section: Bioactive Compounds and Potential Health‐promoting Propertie...mentioning
confidence: 99%
See 1 more Smart Citation
“…These molecules, although effective from 15 to 20% [2]. The very wide uses of medicinal plants for centuries by humans for treating various common pathologies prompted researchers to study the activities and pharmacological properties of different plant metabolites to confirm its properties on the one hand and on the other hand to identify the active ingredients at the origin of these virtues and consequently the use of these natural medicines wisely in primary care systems [3][4][5]. Some plants can be a major source of drugs due to their richness in secondary metabolites, these make and remain the subject of many researches, in particular the research of new natural constituents such as phenolic compounds, saponosides, alkaloids and essential oils [6,7].…”
Section: Introductionmentioning
confidence: 99%